Nursing Interventions for Improving Nutritional Status and Outcomes of Stroke Patients: Descriptive Reviews of Processes and Outcomes. (4th June 2012) - Perry, Lin; Hamilton, Sharon; Williams, Jane; Jones, Susan
ABSTRACT: Background: Stroke produces many effects that impact eating. Nutrition is fundamental for recovery and rehabilitation, but the nursing nutritional role and associated outcomes have not been delineated. Aims: (1) To identify nursing interventions intended to improve nutritional status and related outcomes of stroke survivors, and (2) To examine the outcomes of identified nursing interventions on nutrition‐related outcomes, including dietary intake, functional status, complications, activities of daily living, mortality, and quality of life for stroke survivors. Methods: A modified version of Cochrane literature searching and review methods was used to identify studies that described and evaluated nursing nutritional interventions for adult stroke patients in hospital and community settings. A minimum of 10 years content of seven databases and nine journals was searched to March 2011. Findings were presented descriptively. Results: In total 27 papers from 26 studies were included: 5 randomized controlled trials, 5 clinical trials, 6 quasi‐experiments, 4 case studies, and 6 qualitative/observational studies. Stroke nursing nutritional care encompassed screening of nutritional status and swallowing function; assessment of nutritional characteristics and preferences; referral; mealtime organization, supervision and monitoring; mealtime assistance and feeding skills. Nurses individualized care, coordinated or managed meal delivery and enteral feeding systems, were responsible for the dining environment and conduct of mealtimes; they taught staff, patients, and carers. There was little indication of integrated or psychosocial nursing nutritional care, or concepts, theories or models of nursing nutritional care. Many interventions were described but not evaluated. Little high quality evidence was of available. Conclusions: This review indicated the parameters of nursing nutritional care, and provided a framework for future research. A functional, supportive, and educational nursing nutritional role was described but little evidence was of sufficient quality to support policy and practice development or inform education. Nutritional care was revealed as an essential but under‐recognized element of stroke nursing.